RHEOLOGICAL CHARACTERISTICS OF DRILLING FLUIDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article discusses the rheological properties of a high-density, barite-free drilling mud developed on the basis of formats and polyacrylamide. A comparative analysis with a traditional barite solution is carried out, including an assessment of viscosity and shear stress at different shear rates. It has been established that the non-barite solution has pronounced pseudo-plastic properties, which makes it more effective when drilling horizontal and directional wells. Recommendations for the use and control of the parameters of such solutions under drilling conditions are presented.